2015
DOI: 10.7554/elife.04871
|View full text |Cite
|
Sign up to set email alerts
|

G-actin provides substrate-specificity to eukaryotic initiation factor 2α holophosphatases

Abstract: Dephosphorylation of eukaryotic translation initiation factor 2a (eIF2a) restores protein synthesis at the waning of stress responses and requires a PP1 catalytic subunit and a regulatory subunit, PPP1R15A/GADD34 or PPP1R15B/CReP. Surprisingly, PPP1R15-PP1 binary complexes reconstituted in vitro lacked substrate selectivity. However, selectivity was restored by crude cell lysate or purified G-actin, which joined PPP1R15-PP1 to form a stable ternary complex. In crystal structures of the non-selective PPP1R15B-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
146
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(168 citation statements)
references
References 53 publications
11
146
0
Order By: Relevance
“…Even though the activation level of GCN2 at 1 h of treatment with the depolymerizing drugs was higher than that observed at 1 h of leucine starvation (5-fold increase in GCN2-P levels as compared with 3.5-fold, respectively), eIF2α phosphorylation was lower in response to the drugs relative to that elicited by amino acid depletion (1.5-2.0-fold increase versus 3.5-fold, respectively, taking the 1 h time point). These observations can be interpreted in light of recent evidence indicating that monomeric G-actin provides stabilization of the complex between the catalytic subunit of phosphatase 1 (PP1) and its regulatory subunits, the PPP1R15 proteins, and specificity towards P-eIF2α (Chambers et al, 2015;Chen et al, 2015). Indeed, here in Gcn2 −/− cells, a small decrease in basal P-eIF2α can be detected after latrunculin-B treatment (Fig.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Even though the activation level of GCN2 at 1 h of treatment with the depolymerizing drugs was higher than that observed at 1 h of leucine starvation (5-fold increase in GCN2-P levels as compared with 3.5-fold, respectively), eIF2α phosphorylation was lower in response to the drugs relative to that elicited by amino acid depletion (1.5-2.0-fold increase versus 3.5-fold, respectively, taking the 1 h time point). These observations can be interpreted in light of recent evidence indicating that monomeric G-actin provides stabilization of the complex between the catalytic subunit of phosphatase 1 (PP1) and its regulatory subunits, the PPP1R15 proteins, and specificity towards P-eIF2α (Chambers et al, 2015;Chen et al, 2015). Indeed, here in Gcn2 −/− cells, a small decrease in basal P-eIF2α can be detected after latrunculin-B treatment (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Molecular mechanisms linking the modulation of global protein synthesis to the integrity of the actin cytoskeleton are still poorly understood. Recent reports have indicated that G-actin promotes the stabilization of the complex between phosphatase PP1 and its regulatory subunits, the inducible PPP1R15A (GADD34) or the constitutive PPP1R15B (CReP), that provide the exquisite specificity of this complex towards phosphorylated eIF2α (P-eIF2α) (Chambers et al, 2015;Chen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…PP1-targeting subunits have been proposed to activate the phosphatase activity of PP1 or to target the phosphatase to its substrate (21). Because binding of an RVxF peptide does not appear to alter the conformation of PP1 (22)(23)(24), it seems likely that binding of a regulatory subunit containing an RVxF motif to PP1 is not sufficient to activate PP1 to dephosphorylate a specific substrate. However, in support of the scaffolding role of the PP1-targeting subunits, we previously showed that yeast eIF2γ contains a PP1-binding motif that enables recruitment of the phosphatase PP1/ GLC7 to its substrate eIF2α via the eIF2 complex (25).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these subunits contain the conserved RVxF motif, which has been proposed either to allosterically affect the activity and/or substrate specificity of PP1 or to more simply target PP1 to its substrates (19)(20)(21)(22)(23). Notably, the latter idea is favored because binding of the RVxF motif has not been found to induce a conformational change in PP1 (22)(23)(24). To determine how GADD34 promotes the specific dephosphorylation of eIF2α by PP1, we established a yeast cell-based assay to monitor the dephosphorylation of human eIF2α mediated by the human GADD34-PP1 complex.…”
mentioning
confidence: 97%
“…57 Two recent papers together indicate that G-actin associates with this complex and is required for efficient dephosphorylation of eIF2a. 57,58 Depletion of the G-actin pool with jasplakinolide causes PPP1R15A-PP1 complex destabilization, thereby extending the period of translation arrest. Thus, proper orchestration of the ISR requires integration of signals from the actin cytoskeleton.…”
Section: G-actin Regulates Translation Initiation In Times Of Stressmentioning
confidence: 99%